2015
DOI: 10.1007/s10126-015-9655-7
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-Inducible Factor α and Hif-prolyl Hydroxylase Characterization and Gene Expression in Short-Time Air-Exposed Mytilus galloprovincialis

Abstract: Aquatic organisms experience environmental hypoxia as a result of eutrophication and naturally occurring tidal cycles. Mytilus galloprovincialis, being an anoxic/hypoxic-tolerant bivalve, provides an excellent model to investigate the molecular mechanisms regulating oxygen sensing. Across the animal kingdom, inadequacy in oxygen supply is signalled predominantly by hypoxia-inducible factors (HIF) and Hif-prolyl hydroxylases (PHD). In this study, hif-α 5'-end and partial phd mRNA sequences from M. galloprovinci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
31
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(39 citation statements)
references
References 67 publications
(71 reference statements)
6
31
2
Order By: Relevance
“…The cycling conditions used were as follows: 95°C for 30 s, followed by 40 cycles of 95°C for 5 s and 60°C for 30 s. At the end of the cycling stage, a melt curve analysis was performed to confirm that only one PCR product was amplified. Elongation factor (EF) was selected as the internal control, as described by Du et al (2013) and Giannetto et al (2015) [51, 53]; its expression was observed to be stable in our experiments. The data were then analyzed using the 2 -ΔΔCt method to estimate the relative expression level of the target genes.…”
Section: Methodsmentioning
confidence: 92%
“…The cycling conditions used were as follows: 95°C for 30 s, followed by 40 cycles of 95°C for 5 s and 60°C for 30 s. At the end of the cycling stage, a melt curve analysis was performed to confirm that only one PCR product was amplified. Elongation factor (EF) was selected as the internal control, as described by Du et al (2013) and Giannetto et al (2015) [51, 53]; its expression was observed to be stable in our experiments. The data were then analyzed using the 2 -ΔΔCt method to estimate the relative expression level of the target genes.…”
Section: Methodsmentioning
confidence: 92%
“…They have evolved with various strategies to adapt to such environment, including their enzymatic activities, metabolic rate, and increased surface (gill lamellae) for oxygen exchange (Burggren and Cameron, 1980; Jensen et al, 1993). HIF-1 and HIF-2 are two important regulators for hypoxia responses and oxygen homeostasis (Semenza, 2000; Giannetto et al, 2015). After hypoxia treatment, the HIF genes were differentially expressed in catfish at the transcriptional levels as well, rather than just at the post-translational levels as believed previously (Geng et al, 2014).…”
Section: Part V: Hypoxiamentioning
confidence: 99%
“…Indeed marine molluscs, including the Mediterranean mussel Mytilus galloprovincialis (Lamarck 1819), a very popular shellfish with a wide geographical distribution worldwide (Branch and Stephani, 2004), are commonly included in human diet because of their exceptional nutritional value (Bongiorno et al, 2015;Cappello et al, 2018). Mussels are routinely used as good bioindicators in ecotoxicological studies (Cappello et al, 2017a(Cappello et al, , 2017bGiannetto et al, 2015Giannetto et al, , 2017Maisano et al, 2017) and, due to their filter-feeding habit, are also known to accumulate large numbers of bacteria from the surrounding waters. Albeit mussels possess effective humoral and cellular defence mechanisms against bacterial infection (Canesi and Pruzzo, 2016), some bacteria can be pathogenic to the bivalve host, affecting its physiological performance and in some cases leading to host death (Travers et al, 2015), thus constituting a potential risk also for seafood consumers.…”
Section: Introductionmentioning
confidence: 99%